2021
DOI: 10.5194/acp-21-3193-2021
|View full text |Cite
|
Sign up to set email alerts
|

First validation of GOME-2/MetOp absorbing aerosol height using EARLINET lidar observations

Abstract: Abstract. The aim of this study is to investigate the potential of the Global Ozone Monitoring Experiment-2 (GOME-2) instruments, aboard the Meteorological Operational (MetOp)-A, MetOp-B and MetOp-C satellite programme platforms, to deliver accurate geometrical features of lofted aerosol layers. For this purpose, we use archived ground-based lidar data from stations available from the European Aerosol Research Lidar Network (EARLINET) database. The data are post-processed using the wavelet covariance transform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The methodology is demonstrated using a selected number of collocated cases of TROPOMI overpasses over 215 selected EARLINET lidar stations located around the Mediterranean Basin for the period June 2018 to September 2021. The approach followed is based on the previous expertise and methodology that have been developed using EARLINET observations for the GOME2/MetOp validation activities (Michailidis et al, 2021). At present, seven EARLINET stations operating at 1064 nm (or 532 nm) channel contribute to this study (Figure 1).…”
Section: Validation Methodology and Collocation Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…The methodology is demonstrated using a selected number of collocated cases of TROPOMI overpasses over 215 selected EARLINET lidar stations located around the Mediterranean Basin for the period June 2018 to September 2021. The approach followed is based on the previous expertise and methodology that have been developed using EARLINET observations for the GOME2/MetOp validation activities (Michailidis et al, 2021). At present, seven EARLINET stations operating at 1064 nm (or 532 nm) channel contribute to this study (Figure 1).…”
Section: Validation Methodology and Collocation Criteriamentioning
confidence: 99%
“…With respect to the aerosol layer height reported by UV-VIS satellite sensors,Michailidis et al, (2021) have successfully validated the GOME2/MetOp Absorbing aerosol height (AAH) products using aerosol profiles reported by the EARLINET community. The intercomparison showed that the GOME-2 AAH measurements provide a good estimation of the aerosol layer altitudes sensed by the EARLINET ground-based lidars with a 165 mean bias of approximately −0.2±1.7 km.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The aerosol layers in free troposphere (FT) can be considered as a proxy for their potential to enter PBL and, thus, can directly affect human activity. On the other hand, it is a reliable dataset when used for the validation of the aerosol layer height (ALH) retrieved from satellites (e.g., [7,8]) and of chemistry transport models [9]. Furthermore, they can provide a warning for aviation (e.g., [10]).…”
Section: Introductionmentioning
confidence: 99%